La calidad del servicio financiero y su relación con la satisfacción de los clientes en la cooperativa de ahorro y crédito Luz del Valle agencia Amaguaña. - Casamen Gualotuña, Erik Alexander (2023)
The present project main objective is to analize financial quality service and costumer satisfaction within Cooperative of Savings and Credit Luz del Valle in its agency Amaguaña. For this research was used a qualitative approach and at the same time a quantitative approach. A finite sample of 294 members or customers was taken, where a survey technique was applied to obtain information through a questionnaire using the SERQVAL model and a structured interview was used to organizational development leader of the entity to know current status of quality development of financial service. As results it was possible to identify that, Cooperative Luz del Valle in its quality of service, works with an 85% update in the modernization of its facilities and customer service, in terms of customer satisfaction, not having an internal control evaluation of a SERVQUAL model, the costumers acceptance is 40% that is not very satisfied with the service since the members of the financial entity do not take greater importance to the development of customer service. For this reason, if new improvement actions are not taken, customers will opt for other financial institutions, since customer service is an important factor within financial institutions and can meet quality established standards to achieve the objectives and goals proposed by the company.